The London Auction Mart and the Marketability of Real Estate in England, 1808–1864. (11th March 2016) - Fitz-Gibbon, Desmond
Abstract: This article considers the cultural work of commoditization through the example of the London Auction Mart and the market for real estate in early nineteenth-century England. The auctioneers who founded this exchange sought to reconfigure the organization of property sales in an institution that would bring order and transparency to a world of informal institutions, local markets, and private exchange. The Auction Mart made visible the idea of a universal, abstract property market. At the same time, it offered a new social and cultural space in which to negotiate the often contradictory meanings of marketable property. This work of making the property market meaningful is told through institutional archives, published accounts, diaries, and estate correspondence.